A last resort in cases of wrongful detention and deportation in Africa - Kane, M; Kane, S (Refugee Studies Centre, University of Oxford, 2013)
Where this is no viable forum to address human rights violations by African states, the African Commission on Human and Peoples’ Rights will consider such violations. Its recommendations can then provide a basis on which other actors can put pressure on an offending state to comply with human rights norms